Offensive or defensive play in soccer: a game-theoretical approach - Gambarelli, D.; Gambarelli, G.; Goossens, D. (Journal of Quantitative Analysis in Sports, 2019)
In many sports, such as soccer, a coach has to decide whether to adopt an "offensive" or a "defensive" approach to a match. This strategic decision depends on the strengths and weaknesses of his team with respect to the opponent, but also on the strategy chosen by the opponent`s coach. The fact that a draw also results in a point, which may be important for the ranking, further complicates this decision, as the coach must assess whether it is better to adopt a defensive team formation in order to obtain a draw, or to aim for victory despite the increased risk of defeat. We study this topic by means of a game-theoretical approach, and we develop an algorithm which allows to compute the optimal strategy. The algorithm tests the stability of the outcome with respect to uncertainty in the estimated win probabilities. Furthermore, our approach can handle in-game events, which may provoke changes in optimal strategy. Finally, our model also allows us to assess the effect of various point systems on the willingness of teams to opt for attacking play. Our method is applied to a case study, based on the match Italy - Costa Rica (World Cup 2014).